Tax Conflicts Policy in Thrifting between Trade Law and Tax Law - Efendi Ibnususilo; Faishal Taufiqurrahman; Deslaely Putranti (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
The rapid expansion of thrifting practices in Indonesia has generated complex legal challenges, particularly at the intersection of trade law and tax law. This condition gives rise to a policy conflict in which thrifting activities, although prohibited under trade regulations, continue to generate economic transactions that may fall within the scope of taxation. This study adopts a normative juridical approach to examine the nature of this conflict and to assess potential regulatory responses. The analysis demonstrates that imposing taxation on economic activities derived from prohibited imports creates legal ambiguity and risks undermining the enforcement of trade law by implicitly legitimizing unlawful practices. Accordingly, the principle of legality within the tax system must be upheld by ensuring that taxation aligns with the normative framework governing trade. This study proposes a regulatory harmonization model that integrates trade, taxation, and customs policies through the reconstruction of legal norms, the strengthening of cross sectoral supervision, and the clarification of legal boundaries concerning taxable activities. Such harmonization is necessary to establish legal certainty, prevent regulatory loopholes, and ensure that fiscal policy operates consistently with national legal and economic objectives.